Between Commodification and Emancipation: The Tango Encounter. (May 2017) - Gritzner, Karoline
Abstract : This article offers an examination of the aesthetics and philosophy of Argentine tango, arguing for tango's contradictory power of resistance to the tendency of cultural commodification in contemporary society. The dancing couple achieves a sense of sovereignty and improvisational freedom which is in tension with the increasing commodification and standardisation of art in the age of globalisation. Written partly from an auto-ethnographic, experience-based perspective, the article foregrounds tango's choreography of otherness, relationality, passion and playful improvisation in an attempt to elaborate on tango's significance as a dance of intimate resistance to political economy. What is produced in tango's 'space of touch' remains unproductive, unexplainable, and non-commodifiable. It is argued that Argentine tango might be able to resist total codification due to its improvisational nature and the politics of touch, passion and transgression that emerge from the ephemerality of the encounter, the ineffable 'tango moment'. Tango here is considered as a subversion of the social framing which it nevertheless needs in order to function; it performs the possibility of a transgression, intimately yet publicly.